2020
DOI: 10.1371/journal.pone.0235758
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of risk prediction models for multiple cardiovascular diseases and Type 2 diabetes

Abstract: Accurate risk assessment of an individuals' propensity to develop cardiovascular diseases (CVDs) is crucial for the prevention of these conditions. Numerous published risk prediction models used for CVD risk assessment are based on conventional risk factors and include only a limited number of biomarkers. The addition of novel biomarkers can boost the discriminative ability of risk prediction models for CVDs with different pathogenesis. The present study reports the development of risk prediction models for a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Previous studies on factors and predictive models for CVD have been mostly based on high-quality cohort data obtained by screening or from medical records and patient interviews [11,12]. However, establishing CVD predictive models using clinical data has several limitations.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on factors and predictive models for CVD have been mostly based on high-quality cohort data obtained by screening or from medical records and patient interviews [11,12]. However, establishing CVD predictive models using clinical data has several limitations.…”
Section: Introductionmentioning
confidence: 99%
“…Encompassing non-traditional health data, including anthropometric measurements and lifestyle insights, allows for the assessment of commonly overlooked, yet easily collectable, variables to supplement the already-known clinical factors. The ability to capture a deeper phenotype of the individual prior to infection has proved integral to the model's performance, in line with other disease-specific prediction models developed on the UKB [31][32][33] . Notably, we identified baseline waist circumference, height, weight, and hip circumference to be valuable independent of BMI and obesity, accounting for four of the top-seven RF-ranked features (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 77%
“…Complementing clinical and imaging risk factors, recent research has shown that molecular data can further enhance risk prediction of incident CVD and recurrent events [ 55 , 56 , 57 , 58 , 59 ] as additional risk factors. Moreover, 40–50% of the risk of CAD is heritable [ 60 ], making genotype data in particular a potentially important aspect for predicting and characterizing the risk of recurrent cardiovascular events.…”
Section: Resultsmentioning
confidence: 99%